Sprayed concrete technology : the proceedings of the ACI/SCA International Conference on Sprayed Concrete/Shotcrete, "Sprayed concrete technology for the 21st century" held at Edinburgh University from 10th to 11th September 1996 /: the proceedings of the ACI/SCA International Conference on Sprayed Concrete/Shotcrete, "Sprayed concrete technology for the 21st century" held at Edinburgh University from 10th to 11th September 1996. (2014) - Unknown
No abstract available